Tantangan Berat Penyelesaian Sengketa Kerja Di Tengah Dinamika Ekonomi Digital - Dutasena Mahardhika Hadi (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
The massive development of the digital economy has brought fundamental transformations to Indonesia's employment landscape. The emergence of platform-based business models, the gig economy, and non-conventional employment relationships has created serious challenges in the labor dispute resolution system, which has thus far been based on Law Number 2 of 2004 concerning Industrial Relations Dispute Settlement. This research aims to analyze the juridical challenges in labor dispute resolution in the digital economy era and examine regulatory gaps that affect the protection of workers' rights. The research method used is normative juridical with statutory, conceptual, and case approaches to Industrial Relations Court decisions. The research findings indicate several fundamental challenges, including the unclear legal status of platform workers who are in a gray zone between employees and business partners, the limited absolute competence of the Industrial Relations Court in handling disputes involving cross-jurisdictional digital elements, the weak electronic evidence system in industrial relations dispute cases, and the lack of regulatory harmonization across sectors between labor law, telecommunications law, and personal data protection law. In conclusion, comprehensive labor law reform is needed by creating new categories of employment relationships that accommodate the characteristics of platform workers, strengthening digital evidence mechanisms, and developing adaptive, fast, and affordable alternative dispute resolution mechanisms to ensure legal certainty and protection for both workers and employers in the digital economy era.